Developing, implementing and disseminating a core outcome set for neonatal medicine. Issue 1 (26th July 2017) - Webbe, James; Brunton, Ginny; Ali, Shohaib; Duffy, James MN; Modi, Neena; Gale, Chris
Abstract : Background: In high resource settings, 1 in 10 newborn babies require admission to a neonatal unit. Research evaluating neonatal care involves recording and reporting many different outcomes and outcome measures. Such variation limits the usefulness of research as studies cannot be compared or combined. To address these limitations, we aim to develop, disseminate and implement a core outcome set for neonatal medicine. Methods: A steering group that includes parents and former patients, healthcare professionals and researchers has been formed to guide the development of the core outcome set. We will review neonatal trials systematically to identify previously reported outcomes. Additionally, we will specifically identify outcomes of importance to parents, former patients and healthcare professionals through a systematic review of qualitative studies. Outcomes identified will be entered into an international, multi-perspective eDelphi survey. All key stakeholders will be invited to participate. The Delphi method will encourage individual and group stakeholder consensus to identify a core outcome set. The core outcome set will be mapped to existing, routinely recorded data where these exist. Discussion: Use of a core set will ensure outcomes of importance to key stakeholders, including former patients and parents, are recorded and reported in a standard fashion in future research. Embedding the core outcome set within future clinical studies will extend the usefulness of research to inform practice, enhance patient care and ultimately improve outcomes. Using routinely recorded electronic data will facilitate implementation with minimal addition burden. Trial registration number: Core Outcome Measures in Effectiveness Trials (COMET) database: 842 (www.comet-initiative.org/studies/details/842 ).